The Effect of Workplace Education on Earnings, Turnover, and Job Performance - Krueger, Alan; Rouse, Cecilia (Journal of Labor Economics, 1998)
This article examines the impact of a workplace education program at two companies (one in the manufacturing sector, the other in the service sector). We examine a broad range of outcome variables, including earnings, turnover, performance awards, job attendance, and subjective performance measures. We estimate a small, positive impact of the program on earnings at the manufacturing company but an insignificant impact at the service company. Trainees were equally likely to exit the company as nontrainees. We also find that the training had a positive association with the incidence of job bids, upgrades, performance awards, and job attendance.